WOMEN SAFETY DEVICE - NARAYANA, Dr.V.A; BABU, P.MAHESH; RAVIKIRAN, K.; KUMAR, T.DEVA; AKHILA, G. (The journal of contemporary issues in business and government, 2022)
Women safety has always been an issue even in these modern times with so much advancement in technology. Women are not safe anywhere and are most vulnerable when travelling alone into lonely roads and deserted places. Existing hand held safety devices for women have many disadvantages as they require a software application to be connected with and also should be connected with Bluetooth . So to overcome these disadvantages we propose a solution which will try to overcome the disadvantages of the existing systems and also aim at providing true proof safety to women. The proposed work aims at designing an IoT based safety device that relies on providing security to women by connecting GPS and GSM to locate place and alert message is send to registered numbers when a women is not safe. When there is unsafe situation women can press push button of the device which sends alert message with location automatically to the registered numbers